Desempenho agroeconômico de cultivares de coentro em função de espaçamentos e épocas de cultivo - Lima, Jailma Suerda Silva de (2006)
Two experiments were carried out in the experimental area of the Plant Science Departament at Universidade Federal Rural do Semi-Árido, to evaluate the agroeconomic performance of coriander cultivars as function of spacings and planting times. The first experiment was conducted from June to July of 2005 and the second one from November to December of 2005. The experimental design was randomized complete blocks in a 2 x 12 factorial scheme, with three replications. The treatments consisted of the combination of two coriander cultivars (Verdão and Tabocas) with twelve planting spacings (0.20m x 0.05m, 0.20m x 0.06m, 0.20m x 0.07m, 0.20m x 0.10m, 0.25m x 0.05m, 0.25m x 0.06m, 0.25m x 0.07m, 0.25m x 0.10m, 0.30m x 0.05m, 0.30m x 0.06m, 0.30m x 0.07m and 0.30m x 0.10m). Evaluations of plant height, number of stalks per plant, leaf/stalk ratio, number of marketable bunches per m² and estimated yields of green mass and dry mass were made from the coriander crop. Agroeconomic indicators such as gross and net incomes, rate of return and profit margin were used to assess the coriander cultivars performances. The best agronomic performance and economic efficiency of coriander was observed in Tabocas cultivar and in the planting spacing of 0.20m x 0.05m. The best yield performance of cultivars Tabocas and Verdão was observed in the planting time of November to December and June to July, respectively